2015
DOI: 10.1128/iai.00695-15
|View full text |Cite
|
Sign up to set email alerts
|

Choriodecidual Group B Streptococcal Infection Induces miR-155-5p in the Fetal Lung in Macaca nemestrina

Abstract: eThe mechanisms underlying fetal lung injury remain poorly defined. MicroRNAs (miRNAs) are small noncoding, endogenous RNAs that regulate gene expression and have been implicated in the pathogenesis of lung disease. Using a nonhuman primate model of choriodecidual infection, we sought to determine if differentially expressed miRNAs were associated with acute fetal lung injury. After inoculating 10 chronically catheterized pregnant monkeys (Macaca nemestrina) with either group B streptococcus (GBS) at 1 ؋ 10 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 55 publications
3
24
0
Order By: Relevance
“…In contrast to the miRNAs reported in the previous paragraph, miR-155 was found to act pro-inflammatory in acute lung injury [90], which is in accordance with its role reported in other inflammatory disease. Inducing acute fetal lung injury in a nonhuman primate model of choriodecidual infection, analysis of changes in fetal lung gene expression revealed significant changes in miR-155 expression.…”
Section: Mirnas In Mucosal Immune Functionssupporting
confidence: 85%
See 1 more Smart Citation
“…In contrast to the miRNAs reported in the previous paragraph, miR-155 was found to act pro-inflammatory in acute lung injury [90], which is in accordance with its role reported in other inflammatory disease. Inducing acute fetal lung injury in a nonhuman primate model of choriodecidual infection, analysis of changes in fetal lung gene expression revealed significant changes in miR-155 expression.…”
Section: Mirnas In Mucosal Immune Functionssupporting
confidence: 85%
“…Inducing acute fetal lung injury in a nonhuman primate model of choriodecidual infection, analysis of changes in fetal lung gene expression revealed significant changes in miR-155 expression. Similarly, miR-155 expression level changes have been observed in cytokine stimulated fetal airway epithelial (FeAE) cells [90]. Functional studies using mucosal overexpression of miR-155 led to increased epithelial production of pro-inflammatory cytokines, such as Interleukin-6 (IL-6) and interferon (IFN)-γ inducible protein (CXCL10/IP-10).…”
Section: Mirnas In Mucosal Immune Functionsmentioning
confidence: 99%
“…Furthermore, the authors also found that C/EBPb (CCAAT/enhancer-binding protein beta), a target molecule of miR-155, was associated with IL-10secreting M2-like phenotype of macrophages (Guo et al, 2013a). In support of the above finding, Rao et al (2014) and McAdams et al (2015) illustrated increased expression of miR-155 in SEB (Staphylococcal enterotoxin B) and choriodecidual group B streptococcal infected lungs, respectively. Rao et al (2014) compared the development of ALI in wild-type and miR-155 À/À mice and found that miR-155 À/À had diminished inflammatory cytokines production and inflammatory cells accumulation in SEB-infected lungs.…”
Section: Taqman Low Density Arraysmentioning
confidence: 66%
“…Interestingly, this finding is in agreement with the report of Androulidaki et al () that miR‐155 mimic suppresses SOCS1 expression in vitro. Later, McAdams et al () showed that over‐expression of miR‐155‐5p in fetal airway epithelial cells in turn increased the production of IL‐6 and CXCL10/IP‐10 (C‐X‐C motif ligand 10), which are implicated in leukocyte recruitment. Together, these studies suggested an important role for miR‐155 in promoting inflammation in the lungs in response to different injury models.…”
Section: Regulatory Role Of Mirnas In the Pathogenesis Of Ali/ardsmentioning
confidence: 99%
“…Fetal lung injury can also be caused by GBS-induced chorioamnionitis without bacterial invasion [38, 105]. Also, increases in amniotic fluid cytokines contributes to fetal lung injury [38], and dysregulation of fetal lung development [105] [106]. Moreover, intra-amniotic administration of MVs leads to significantly increased rates of fetal damage and preterm birth [84].…”
Section: Host Determinants Of Gbs Vaginal Colonization Ascending Infmentioning
confidence: 99%